PENGARUH INFORMASI KEUANGAN DAN NON KEUANGAN PADA RETURN AWAL PERUSAHAAN YANG MELAKUKAN IPO - Dwijayanti, Made Indira; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
IPO is an activity of a company before enter the secondary market. The stocks will be traded to the investor which is invest in a capital market.The initial price should be dealed between the company and the underwriter.The aim of this research is to test the affects of Price Earnings Ratio, Debt to Equity Ratio, Zise, Auditor and Underwriter reputation to initial return. This research is conducted at BEI in the the period 2008 – 2012 based on Indonesian Capital Market Directory and prospectus, with purposive sampling method, the sample is 71 firms (bank exclude). The result of this research find that Price earnings ratio and Auditor reputation has positive and significant effect to initial return. Otherwise underwriter reputation has consistet effect but not significant to intial return. While Debt to Equity Ratio and Size has not consistent effect and not significant effect.
Keywords: price earnings ratio, debt to equity ratio, size, reputation auditor, reputation of underwriter, initial return